Construction of gene cassette harboring HMW glutenin gene of wheat driven by γ-kafirin promoter of sorghum - Mishra, Avinash (Acta Biologica Szegediensis, 2008)
Modern biological tools of genetic engineering and biotechnology can allow transfer of gene(s) across crop species. The r-DNA technology has tremendous potential to transfer bread making character of bread wheat into sorghum by transferring glutenin gene(s), which can improve the visico-elastic property of the sorghum flour/dough. These genes in addition to improving quality can significantly contribute to improve the nutritional status by the addition of more protein fractions also. In the simplest approach, new HMW gluten loci may be created via transformation to bioengineer sorghum quality. For this, amplified γ-kafirin promoter (574 bp) was subcloned in pCAMBIA1304 by replacing CaMV35S promoter (ca. 800 bp) of the gus reporter gene resulting in vector pkaf-gus, where the expression of gus reporter gene is under the control of γ-kafirin promoter. In order to construct a gene cassette where HMW glu gene(s) will be under the control of γ-kafirin gene promoter, kafirin promoter was first cloned in pUC19 and then HMW gene(s) were excised from their respective vectors and cloned under the control of promoter. Finally, two gene cassettes were developed as pKaf-Dx5 and pKaf-Dy10 where expression of the HMW glu gene Dx5 (8.7 kb) and Dy10 (6.4 kb) was driven by the γ-kafirin gene promoter. Both gene cassettes are ready to clone in any vector to bioengineer sorghum by genetic transformation.